2016
DOI: 10.1371/journal.pone.0153312
|View full text |Cite
|
Sign up to set email alerts
|

P21-Activated Kinase Inhibitors FRAX486 and IPA3: Inhibition of Prostate Stromal Cell Growth and Effects on Smooth Muscle Contraction in the Human Prostate

Abstract: Prostate smooth muscle tone and hyperplastic growth are involved in the pathophysiology and treatment of male lower urinary tract symptoms (LUTS). Available drugs are characterized by limited efficacy. Patients’ adherence is particularly low to combination therapies of 5α-reductase inhibitors and α1-adrenoceptor antagonists, which are supposed to target contraction and growth simultaneously. Consequently, molecular etiology of benign prostatic hyperplasia (BPH) and new compounds interfering with smooth muscle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 73 publications
1
41
0
Order By: Relevance
“…Similarly, PSA was detected in almost all prostate samples included to these analyses, with very obvious variations of PSA content between prostates from different patients (Figure B). Together, this may reflect individual variations, and/or different degree of hyperplasia, as recently described (Kunit et al ., ; Wang et al ., ; ,b). Calponin, but not pan‐cytokeratin, was detectable in WPMY‐1 cells (Figure C), confirming the smooth muscle‐like phenotype of these cells (Wang et al ., ).…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Similarly, PSA was detected in almost all prostate samples included to these analyses, with very obvious variations of PSA content between prostates from different patients (Figure B). Together, this may reflect individual variations, and/or different degree of hyperplasia, as recently described (Kunit et al ., ; Wang et al ., ; ,b). Calponin, but not pan‐cytokeratin, was detectable in WPMY‐1 cells (Figure C), confirming the smooth muscle‐like phenotype of these cells (Wang et al ., ).…”
Section: Resultsmentioning
confidence: 96%
“…EC 50 values in organ bath experiments and in intact tissues may be higher than IC 50 values in biochemical assays, for example, due to divergent access of inhibitors to their targets resulting from barriers like membranes or connective tissue (Vauquelin et al ., ; Swinney, ; Kunit et al ., ; Wang et al ., ). In fact, EC 50 values for biological effects of LIMK inhibitors in previous studies were higher than IC 50 values in kinase assays, so that migration of prostate cancer cells was inhibited by 100 nM SR7826 by 16% and by 74% by 1 μM (Yin et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It has been reported that the IPA3 inhibitor has a lower potency compared to ATP-competitive inhibitors, such as FRAX597 (Kim et al, 2016;Semenova and Chernoff, 2017). Other studies used also a 10-fold difference between these two inhibitors (Wang et al, 2016). Cells were cultured 72 h, fixated with 2.5% glutaraldehyde solution (Serva, Heidelberg, Germany) and stained with 4 µg/ml of the Hoechst 33342 dye (Serva, Heidelberg, Germany).…”
Section: Analysis Of 3d Motility Within Extracellular Matrix Scaffoldsmentioning
confidence: 99%
“…This link may include SFKs, which may affect contractility and growth concurrently by regulation of actin dynamics. Notably, other compounds may affect contraction and growth at once in the prostate as well, including inhibitors for Rho kinase, Rac GTPases or p21‐activated kinases, what may additionally point to this link (Rees et al, ; Wang et al, ; Wang et al, ). Together, the idea of such a connection may appear attractive, as both processes, that is contraction and growth, are important targets for medical therapy of BOO (Oelke et al, ).…”
Section: Discussionmentioning
confidence: 99%